Innate ability, health, motivation, and social capital as predictors of students’ cognitive, affective and psychomotor learning outcomes in secondary schools - Owan, Valentine Joseph; Ekpenyong, John Asuquo; Chuktu, Onyinye; Asuquo, Michael Ekpenyong; Ogar, Joseph Ojishe; Owan, Mercy Valentine; Okon, Sylvia (Frontiers in Psychology, 2022)
Background: Previous studies assessing students' learning outcomes and identifying contributing factors have often dwelt on the cognitive domain. Furthermore, school evaluation decisions are often made using scores from cognitive-based tests to rank students. This practice often skews evaluation results, given that education aims to improve the three learning domains. This study addresses this gap by assessing the contributions of four students' input to their cognitive, affective and psychomotor skills (CAPs). Methods: A cross-section of senior secondary class II students (n = 870), sampled through the multistage procedure, participated in a physical survey. Students' Inputs Questionnaire (STIQ) and Learning Outcomes Questionnaire (LOQ) were used for data collection. Based on data obtained from a pilot sample (n = 412), principal axis factoring (PAF) was performed to assess the internal structure of the instruments following an oblique rotation. The KMO value of sampling adequacy were .88 and .94, while the Bartlett’s test of sphericity were significant χ2(253) = 5010; p < .001 and χ2(105) = 3693.38, p < .001 for the STIQ and LOQ respectively. Confirmatory factor analysis was used to assess the model acceptability based on the maximum likelihood estimation technique. The main study used hierarchical linear regression for data analysis. Results: Findings indicated that innate ability, health, motivation and social capital relatively and cumulatively predicted students' overall, cognitive, affective and psychomotor learning outcomes. The proportion of variance explained by the predictors increased at different levels of the models with the addition of new variables. Students' social capital reduces the effect of students' innate ability regardless of their motivation and health status. Conclusion/implication: This study has provided evidence that the four students' inputs are crucial predictors of their learning outcomes in the three domains. This result is helpful for school management to provide services aimed at improving the school climate for students' motivation and social capital. The result can provide policymakers with a proper understanding of the constituents of learning outcomes and how policies can be aligned to secure quality student inputs for maximum productivity in education.